Wafer container monitoring concerning airborne molecular contaminations along a 300 mm power semiconductor production flow - Franze, Peter; Schneider, Germar; Kaskel, Stefan (Solid State Phenomena, 2021)
The focus of the study was to understand the behavior of airborne molecular contaminations (AMC) within the 300 mm wafer containers called front-opening unified pods (FOUPs) in a high-volume fabrication facility for power semiconductors of Infineon Technologies Dresden. A main goal was to implement new concepts and strategies to prevent the different power semiconductors from any yield losses driven by AMC. It could be shown, that there is a strong dependency of the concentration and the type of the determined contaminations on the investigated process steps.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Airborne molecular contamination; AMC; Chemical analysis; CRDS; Electrochemical conductivity measurements; FOUP; FOUP management; Mass spectroscopy; Power semiconductors